Efeito do alto sódio no fenótipo migratório de células musculares lisas vasculares de aorta de ratos - Brun, Bruna Ferro (2017)
INTRODUCTION: In the cardiovascular system, the migration of vascular smooth muscle cell migration (VSMC) is fundamental in processes such as angiogenesis, vasculogenesis, and in response to injuries in the process of vascular remodeling. High sodium (HS) has been associated with the development of cardiovascular diseases, regardless the increase in blood pressure. However, little is known about their effects in migration of VSMCs and the possible mechanisms involved. OBJECTIVE: To test the hypothesis that high sodium concentration can induce phenotypic changes in VSMCs and to evaluate the molecular mechanisms that may be involved in this process. METHODS: Primary vascular smooth muscle cells were obtained by the explant method. Cellular migration was evaluated by the Wound-Healing method under the conditions: High Sodium (AS, NaCl: 160 mM) and Control (CT, NaCl: 140 mM) and the following drugs were used: Candesartan, Enalapril, Tiron, Angiotensin II, NS398, Apocinin, SQ29548, U46619, CAY10441 and U0126 (N = 5 to 7). Cell viability was assessed by Annexin V and PI labeling. The gene expression of cyclooxygenase-2 (COX-2) was analyzed by RT-PCR. Protein expression of phosphorylated ERK 1/2 was assessed by the Western Blot. RESULTS: Pre-exposure of CMLVs to HS reduced migration (CT: 100 ± 14% / HS: 58 ± 11%), without modifying cellular viability. Blocking of the AT1 receptor with Candesartan prevented the action of HS in cell migration (* HS + Candesartan: 101 ± 10%), as well as the blockade of ACE by Enalapril (* HS + Enalapril: 97 ± 5%). Blockade of COX-2 with NS398 also prevented the action of HS (* HS + NS398: 96 ± 7%). Blocking of ERK 1/2 with U0126 also reversed the action of HS (* HS + U0126: 99 ± 5%), as well as the thromboxane receptor blockade with SQ29548 (* HS + SQ29548: 94 ± 10%). HS increased the gene expression of COX-2 and ERK1 / 2 phosphorylation. AT1 receptor blockade normalized COX-2 gene expression and prevented the increase of ERK 1/2 phosphorylation. Inhibitor of the MEK 1/2 prevented the increase of COX-2 gene expression. CONCLUSION: The study demonstrated that HS reduces the migration of vascular smooth muscle cells by increasing COX-2 expression via the AT1 receptor through ERK 1/2 phosphorylation. In addition, the increase of COX-2 by HS seems to modulate the reduction of migration of VSMCs by the increase of thromboxane.